Padangsidimpuan City Traders' Economic Assistance With Julo-Julo - Replita Replita; Nursyirwan Effendi; Taufika Ophiyandri; Alfan Miko; Jumadi Jumadi; Sri Fatimah Hasibuan; Ali Hardana (SPT. haria Journal and Education Center Publishing, 2026)
The purpose of this study is to find out the types of social exchanges in Julo-Julo activities and how social exchanges function in terms of economics. This research was conducted with a qualitative approach and phenomenological methods. Observations, interviews, and documentation are used to collect data. The theory of reciprocity is the theory used in this study. According to information collected from the Julo-Julo social exchange at the Sangkumpal Bonang Market, Padangsidimpuan City, wedding and celebration materials used by Julo-Julo members for weddings and celebrations were collected by the chairman of the Julo-Julo board. The Julo-Julo method uses staples according to criteria, where the criteria are the most important members of Julo-Julo, which is to meet material needs. In society, there are two types of exchange: comparative reciprocity and general reciprocity. The function of the Julo-Julo exchange for the community in the Sangkumpal Market, Padangsidimpuan City is to overcome problems related to holding weddings and celebrations, such as a lack of money capital, a lack of rewang labor, and a lack of facilities and infrastructure.